Thematic Analysis of My “Coming Out” Experiences Through an Intersectional Lens: An Autoethnographic Study - Leung, Enoch (Frontiers in Psychology, 2021)
For lesbian, gay, bisexual, transgender, and queer (LGBTQ) youth, identity development is one of the most critical developmental task. LGBTQ youth are shown to be at risk for a variety of risk factors including depression and suicidal ideation and attempts due to how their identities are appraised in heteronormative societies. However, most LGBTQ educational psychology research have highlighted protective factors that are primarily relevant to support LGBTQ white-youth. One of the major developmental theories, Erikson’s stages of psychosocial development, has identified adolescence as the period where identity development occurs. However, through an intersectional lens, identity development appears to encompass more than adolescence but also emerging adulthood, a developmental stage not accounted for by Erikson’s stages of psychosocial development. The primary goal of this study is to seek to understand and question Erikson’s stages of psychosocial development through an intersectional lens of an autoethnography of my LGBTQ experiences. An autoethnographic approach (diary entries [N = 9], conversations [N = 12], interview [N = 1], social media websites and blogs [N = 2], and drawing [N = 1]) is used to understand my LGBTQ-person of color (POC) experiences of “coming out” or self-disclosure during my adolescence through emerging adulthood. Data was collected on April 2020 and spanned from 2006 through 2020 to account for the developmental period of adolescence and emerging adulthood (ages 13 through 27). Thematic analysis revealed four themes across the two developmental periods: 1) confusion and conflict between my gay and ethnic identity as a closeted adolescent, 2) my first “coming out” as a gay adolescent and “it got better”, 3) frustration arising from the internal conflict between my gay and POC identity as an emerging adult, and 4) frustration arising from external experiences with the flaws of LGBTQ community inclusivity. Results reflected a continuous theme of identity exploration and struggle through both adolescence and emerging adulthood, highlighting the need for future research to replicate similar experiences from other intersectional individuals during emerging adulthood stage, a developmental stage that is considered in between Erikson’s adolescent and young adulthood developmental stage.